The Personality Brokers: The Strange History of Myers-Briggs and the Birth of Personality Testing - Muldoon, Jeffrey (Relations industrielles / Industrial Relations, 2020)
The article reviews the book, "The Personality Brokers: The Strange History of Myers-Briggs and the Birth of Personality Testing," by Merve Emre.